PENGARUH TERPAAN TEASER WEBCOMIC THE VILLAINESS IS A MARIONETTE TERHADAP BRAND AWARENESS KAKAO WEBTOON (STUDI KASUS REMAJA DI KOTA DENPASAR) - Kusumayani, Ni Komang Leni; Pradipta, Ade Devia; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium, 2024)
Video marketing is one of the most used types of advertising today. Kakao Webtoon is a digital comic platform that often releases unique and creative advertisements for their products in the form of video marketing. The teaser webcomic The Villainess Is A Marrionette is one of Kakao Webtoon's video marketing advertisements that has managed to attract attention because it is the first visual dramatization advertisement that was worked on for a webtoon advertisement, and involves famous South Korean actors/actresses such as Cha Eun Woo, Han Soo Hee and Lee So Hyuk. This study uses Stimulus Organism Response (SOR) theory with a quantitative approach and associative problem formulation. The purpose of this research is to determine the impact of exposure to the teaser webcomic The Villainess Is A Marrionette on Kakao Webtoon's brand awareness for teenagers in Denpasar City. The conclusions of the analysis indicate that the teaser webcomic The Villainess Is Marrioentte has formed a brand awareness of teenagers in Denpasar City towards Kakao Webtoon.